Bladder Injury: A complication of Transobturator Tape Surgery - Shrestha, Alka; Dangal, Ganesh; Tiwari, Kenusha Devi (Nepal Journal of Obstetrics and Gynaecology, 2021)
Minimally invasive vaginal surgeries are often a preferred mode of surgical treatment of stress urinary incontinence. It is associated with fewer complications. However, complications including hemorrhage, voiding dysfunction, infection, pain, skin infection and erosion, and bladder injuries are observed. We encountered intraoperative bladder injury in a 40-year-old female patient with stress urinary incontinence who underwent transobturator tape (TOT) surgery. Cystoscopy demonstrated a small defect post procedure. She was managed conservatively with foley catheterization for 2 weeks following TOT procedure. She was dry and continent upon follow up.